2019
DOI: 10.14202/vetworld.2019.1833-1839
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of viral interference among Egyptian isolates of highly pathogenic avian influenza viruses (H5N1 and H5N8) with the lentogenic and velogenic Newcastle disease virus genotype VII in specific pathogen-free embryonated chicken eggs model

Abstract: Background and Aim: Mixed infections of the highly pathogenic avian influenza virus (HPAIV) and Newcastle disease virus (NDV) are considered the most distressing problem of the poultry industry. The problem arises due to the influence of a hidden virus on the replication of another suspected virus. Consequently, misdiagnosis of the real cause of disease may become a source of infection for other healthy stock by transmission and dissemination of the hidden virus. This study aimed to determine the impact of HPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In the present study, as shown in (Tables 3, 4) the highest obtained results for respiratory viruses was AIV (12/15) of both single infection (6/15) 3 broilers and 3 layer flocks and mixed infection with NDV (6/15) 4 broilers, 1 layer and 1 breeder flocks, similar results were reported by Soliman et al [32] who mentioned that the mixed infections of AIV and NDV was one of the most distressing problem of the poultry industry worldwide. The infection with some viruses is considered as a great stress to the birds and is considered as the main cause of co-infection and also it facilitated the infection with other viruses Arafat et al [17], Samy and Naguib [33], Watanbe et al [34].…”
Section: Molecular Identification By Real Time Rt-pcr Testsupporting
confidence: 91%
“…In the present study, as shown in (Tables 3, 4) the highest obtained results for respiratory viruses was AIV (12/15) of both single infection (6/15) 3 broilers and 3 layer flocks and mixed infection with NDV (6/15) 4 broilers, 1 layer and 1 breeder flocks, similar results were reported by Soliman et al [32] who mentioned that the mixed infections of AIV and NDV was one of the most distressing problem of the poultry industry worldwide. The infection with some viruses is considered as a great stress to the birds and is considered as the main cause of co-infection and also it facilitated the infection with other viruses Arafat et al [17], Samy and Naguib [33], Watanbe et al [34].…”
Section: Molecular Identification By Real Time Rt-pcr Testsupporting
confidence: 91%
“…Previous studies have shown that the first virus is capable of inhibiting the growth of another (Roussan et al 2008& Pantin jackwood et al 2015. Previous study was focused on the evaluation of the interference between AIV and NDV using qrRT-PCR to determine the degree of viral competence, also it showed high replication competence for H5N8 against H5N1 after sequential infection of H5N1 and H5N8 based on quantitative evaluation of hemagglutinin (H) gene (Soliman et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for high incidence of mixed infections of different viral diseases as AIV and Newcastle dis virus was provided by several studies (Amer et al 2018& El-lakany et al 2018.The likelihood of viral competence between AIV and Newcastle disease virus (NDV) co-infection was discussed by a previous study (Soliman et al 2019). The study has provided an evidence of replication competence between AIV H5N1 and H5N8 that revealed higher replication competence of H5N8 against H5N1 as well as both AIV strains showed higher replication competence against NDV that was based on quantitative evaluation of hemagglutinin (HA) gene in-vitro infection in SPF-ECE (Soliman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research into NDV is done as viral challenge models in chickens or in ovo using SPF embryonated chicken eggs, but the strain of chicken and the precise definition of SPF are not often disclosed [444,[478][479][480][481][482][483]. The most commonly reported strain of chicken used is the White Leghorn, along with others such as White Rock and Isa Brown layers [120,447,[484][485][486].…”
Section: Newcastle Diseasementioning
confidence: 99%